The Role of Internalized Homophobia and Distress in Gay Men's Attitudes Towards Seeking Psychotherapy/MSc Integrative Counceling and Psychotherapy: Individual Research Project - Poulitsas Nikolaos; Zachariadis Andreas Polydoros (2019)
Introduction, Literature Review, Internalized Homophobia and Attitudes Towards Homosexuality, Gay Affirmative Psychotherapy, Gay Affirmative Cognitive Behavioural Psychotherapy, Attitudes Towards Seeking Psychotherapy, Age, Coming Out and Sexual Orientation, Self Disclosure and Self Concealment Disclosure, Hypotheses, Method, Design, Participants, mMaterials, Procedure, Ethics, Results, Discussion, Hypotheses Discussion, Limitations, Strengths, Future Research, Conclusion, References, Appendices, Invitation Letter, Briefing, Consent Form, Internalized Homophobia Scale, Distress Disclosure Index, Attitudes Towards Seeking Professional Psychological Help Scale, Debriefing, Statistics.